A Study on the Effects of Chinese Yuan's Appreciation on Hong Kong's Economic and Financial Markets - Lai, Hoi Wah Katherine (2008)
The Chinese Yuan (RMB) has been appreciating persistently in the past years and this rise in value is expected to continue in the next decade. Although Hong Kong is a Special Administrative Region in China after the handover in 1997, its currency is still adopting the fixed exchange rate system against the US Dollar (USD), which is experiencing continuous depreciation in the past few years. This contradiction has serious implications on Hong KongÃÂÃÂ¢ÃÂÃÂÃÂÃÂs economic and financial markets both in the near future and in the long run. In the past few months, there has been a flood of HK dollars (HKD) deposited in local banks switching over to RMB causing tremendous pressure on the Hong KongÃÂÃÂ¢ÃÂÃÂÃÂÃÂs financial system. ChinaÃÂÃÂ¢ÃÂÃÂÃÂÃÂs top financial officials have warned against the rising tide of RMB and, as a temporary measure to stop the fleeing, have widened the buying and selling rates for exchanging between RMB and HKD.